2015
DOI: 10.1136/thoraxjnl-2015-206784
|View full text |Cite
|
Sign up to set email alerts
|

Review of the British Thoracic Society Winter Meeting 2014, 3-5 December, London, UK

Abstract: The British Thoracic Society Winter Meeting 2014 is reviewed in this article. This annual scientific meeting attracted its largest number of delegates ever and over 3 days in December up-to-date respiratory research was presented and current thinking in respiratory science and clinical academia was discussed. This article reviews a number of symposia and selected abstract presentations from the meeting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Her group previously reported that vitamin D deficiency appears to contribute to the development of acute respiratory distress syndrome (ARDS)3 and now demonstrate that vitamin D supplementation reduces perioperative extravascular lung water but not oxygenation 1. The immunomodulatory effects of vitamin D (or the absence of them) have been a recurring theme of our 3 years reporting from the BTS Winter Meeting and we look forward to large confirmatory studies 4 5. Dr Richard Lee (King's College London) was the runner up in the BLF competition for his study evaluating MET targeted therapy in non-small cell lung cancer 6…”
Section: Introductionmentioning
confidence: 86%
“…Her group previously reported that vitamin D deficiency appears to contribute to the development of acute respiratory distress syndrome (ARDS)3 and now demonstrate that vitamin D supplementation reduces perioperative extravascular lung water but not oxygenation 1. The immunomodulatory effects of vitamin D (or the absence of them) have been a recurring theme of our 3 years reporting from the BTS Winter Meeting and we look forward to large confirmatory studies 4 5. Dr Richard Lee (King's College London) was the runner up in the BLF competition for his study evaluating MET targeted therapy in non-small cell lung cancer 6…”
Section: Introductionmentioning
confidence: 86%